Analisis Faktor Yang Mempengaruhi Minat Nasabah Dalam Menggunakan Pembiayaan Murabahah Di BMT Anugrah Kecamatan Batang Kuis Kabupaten Deli Serdang - Hasibuan, M. Yusuf; Fadhila Rahma, Tri Inda; Armayani Hasibuan, Reni Ria (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of Service, location and promotion of customer interest using murabahah financing at BMT Anugrah Batang kuis. This type of research is a qualitative research with the source data used is primary data. Samples were selected using the slovin formula, the number of samples in this study was 40 respondents using data processing and analysis techniques, multiple linear regression analysis, classical assumption Test and hypothesis test. The Program used for calculations using SPSS version 25 and then the results of the SPSS is interpreted. Partially Service significantly positive effect on customer interest in using murabahah financing in bmt anugrah Batang kuis district deli serdang. This is evidenced by the value of sinifikansi 0,001 < 0,05 and the value of thitung 2,432 > ttable 1,68830, partially location significant positive effect on customer interest in using murabahah financing in bmt anugrah Batang kuis district deli serdang. This is evidenced by the value of sinifikansi 0,000 < 0,05 and the value of thitung 2,112 > ttable 1,68830. Partially, the promotion has a significant positive effect on customer interest in using murabahah financing in bmt anugrah batang kuis district deli serdang regency. This is evidenced by the value of sinifikansi 0.000 < 0.05 and the value of thitung 1.900 > ttable 1.68830. Simultaneously service, location and Promotionsignificant influence on customer interest in using murabahah financing in bmt anugrah batang kuis district deli serdang. This is evidenced by the significance value of 0.001 < 0.05 and the value of F count 5.265 > F Table 2.860.